349. Retrospective Descriptive Analysis of West Nile Neuroinvasive Disease in Northwest Louisiana. (26th November 2018) - Mada, Pradeep; Sneed, Philip; Castano, Gabriel; Moore, Maureen; Chandranesan, Andrew Stevenson Joel
Abstract: Background: West Nile virus (WNV) infection has become endemic in the continental United States. Eighty percent of the West Nile virus infections are asymptomatic. One in 150 individuals with West Nile virus infection develops West Nile neuroinvasive disease (WNND). The neurological manifestations include encephalitis, meningoencephalitis, meningitis, and acute flaccid paralysis. Methods: We performed a retrospective descriptive study in our tertiary care hospital in Louisiana to describe the clinical features, Cerebrospinal fluid (CSF) findings and clinical outcomes. Patients aged >18 years admitted in our hospital between January 1, 2012 and December 31, 2017 were included. Hospital Electronic Health records were screened for diagnosis of WNND by ICD codes and positive WNV antibody testing in CSF. Results: There were a total of 23 patients identified with positive WNV IgM or IgG in CSF. Fifteen patients were males and eight were female. The median age was 48.8 years. Six patients were diagnosed with meningitis, 12 with encephalitis, and five with meningoencephalitis. Most Common presenting symptoms were altered mental status and fever in 15 patients. Only two patients gave history of mosquito bite. Incidence was peak in the month of August, July, and September. WNV IgG and IgM antibodies were positive in CSF in 13 patients. Four patients had only positive WNV IgM and six patients had only positive WNV IgG. The average number of days from the admission to diagnosis of infection ranged from 3 to 16 days with average of 8.9 days. CSF protein was >45 mg/dL in 12 patients and elevated white cell count (>5 mm 3 ) in 20 patients. CSF protein >100 mg/dL was seen in nine patients. Lymphocytosis was present in 10 patients. The average length of stay was 13.3 days and nine patients required ICU stay. Only one patient was not given any antibiotics. The average duration of antibiotics was 6.4 days. On 1 year follow-up, eight patients had no residual deficits, four patients had residual deficits, two patients were deceased, and nine patients were lost to follow-up. Conclusion: WNV infection has become endemic in Southern United States especially in summer months. Identifying the infection early in its clinical course would help to avoid unnecessary antibiotics when patients present with fever and meningeal symptoms. Including WNV antibodies in CSF studies is critical in making a diagnosis. Disclosures: All authors: No reported disclosures.